Potensi Air Tanah Di Wilayah Pengungsian Erupsi Gunung Agung Bali - Yan Adhitya Wesda Wardhana; Isnan Fauzan; Heni Rengganis (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2019)
Gunung Agung is a stratovolcano type of volcano which has a height of 3,142 masl and is located in Karangasem Regency, Bali Province. At the end of 2017, Mount Agung's volcanic activity increased until it finally erupted several times in October to December. The government has prepared refuge pockets at the foot of Mount Agung, in areas that are not directly affected by eruption. There are 19 drilling plan points that will be carried out to meet the raw water needs at the evacuation site. This paper presents the groundwater recharge potential including the distribution of water sources, Hydrogeological conditions and the magnitude of groundwater recharge potential at hillside of Mount Agung and the surrounding area. The method used in this study is a field survey, calculation of potential recharge, analysis and evaluation of hydrogeological conditions, distribution of water sources and calculation of potential groundwater recharge. Groundwater at the foot of Mount Agung has the potential to be utilized and developed mainly to cover raw water needs in several refugee locations, namely in the Districts of Sidemen, Abang and Karangasem. The result of the analysis is that the largest groundwater potential is in Kubu Sub-District, namely 97,560,207 m3 / year, with a position that is relatively susceptible to primary hazards and secondary to Mount Agung eruption. For locations that are relatively safe and reachable in the area, they are in Tianyar, Sukadana, Baturinggit, Kubu, and Tulamben Villages, all of which are on the coast of the sea. These results are expected to be used by local governments in an effort to deal with the provision of water from the impact of the eruption of Mount Agung.